Describe the transformation that made for the following terms. (a) \(\displaystyle{f{{\left({x}\right)}}}=-{3}{\log{{\left({2}{x}\right)}}}\)

\(a=-3, k=2\)

(b) \(\displaystyle{f{{\left({x}\right)}}}={\log{{\left({x}-{5}\right)}}}+{2}\)

\(d=5, c=2\)

(c) \(\displaystyle{f{{\left({x}\right)}}}=\frac{{1}}{{2}}{\log{{\left({5}{x}\right)}}}\)

\(a=\)\(\displaystyle\frac{{1}}{{2}}\), \(k=5\)

(d) \(\displaystyle{f{{\left({x}\right)}}}={\log{{\left(-{\left(\frac{{1}}{{3}}\right)}{x}\right)}}}-{3}\)

\(k=\)\(\displaystyle-{\left(\frac{{1}}{{3}}\right)}\), \(c=-3\)